Regularidade para equações quase lineares em conjuntos singulares degenerados - Oliveira Filho, Narcélio Silva de (2015)
We will study a new universal gradient continuity estimate for solutions to quasi-linear equations with varying coefficients at singular set of degeneracy: S(u) := {X : Du(X) = 0}. Ourmain theorem reveals that along S(u), u is asymptotic as regular as solutions to constant coefficient equations. In particular, along the critical set S(u),u enjoys a modulus of continuity much superior than the possibly low, continuity feature of the coefficients. The results are new even in the context of linear elliptic equations, where it is herein shown that H^1- weak solutions to div (a(X,Du))= 0 with aij elliptic and dinicontinuous are actually C ^{1,1^{-}} along S(u). The results and insights of this work foster a new understanding os smoothness properties of solutions to degenerate or singular equations, beyond typical elliptic regularity estimates, precisely where the diffusion attributes of the equation collapse.